Bibliometric Study of the National Scientific Production of All Peruvian Schools of Dentistry in Scopus. (17th April 2021) - Mayta-Tovalino, Frank; Pacheco-Mendoza, Josmel; Diaz-Soriano, Ana; Perez-Vargas, Fernando; Munive-Degregori, Arnaldo; Luza, Silvia
Abstract : Objective . To perform a bibliometric analysis of the national scholarly output of all dental schools in Peru in Scopus through a retrospective study after the promulgation of the Peruvian University Law 30220 in 2014. Methods . This was a descriptive, comparative, retrospective, and cross-sectional study. A search of the Scopus database was performed to identify scholarly output in dentistry between 2014 and 2019. A total of 287 scientific articles with affiliation with the dental faculties of Peruvian public and private universities were evaluated. The data was extracted from Scopus using a complex formula developed from the words of the thesaurus MeSh (Medline) and Emtree (base) with words related to dentistry combined with the AF-IDs of the Peruvian universities. Results . The Top 10 in the scholarly output of all the Peruvian public and private dental schools were as follows: firstly, the Universidad Peruana Cayetano Heredia (UPCH), with 79 scholarly outputs publications and 5.2 citations per article, followed by the Universidad Nacional Mayor de San Marcos (UNMSM) with 53 scholarly outputs publications and 2.6 citations per article, and in third place, the Universidad Cientifica del Sur (UCSUR) with 49 scholarly outputs publications. In general, it was found that, of the 30 Faculties of Dentistry in Peru, only 10 in the public and private universities have a scholarly output greater than 5 to belong to the top 10. In addition, it was found that, according to the share of publications per journal quartile by the CiteScore Percentile of all the public and private Peruvian Faculties of Dentistry, in 2019, it presented the highest number of scientific publications in all quartiles with 20, 33, 14 and 43 articles in the quartiles Q1, Q2, Q3, and Q4, respectively. The highest number of scientific publications was produced in 2019 with 20, 33, 14, and 43 articles in quartiles Q1, Q2, Q3, and Q4, respectively. Conclusion . The UPCH, UNMSM, and UCSUR dental schools were the most productive. Both public and private universities presented an evident increase in their scientific publications in Scopus after the promulgation of the University Law 30220 in 2014.